2018
DOI: 10.1080/10962247.2018.1536004
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption kinetics and modeling of H2S by treated waste oil fly ash

Abstract: Waste oil fly ash (OFA) collected from disposal of power generation plants was treated by physicochemical activation technique to improve the surface properties of OFA. This synthesized material was further used for potential hydrogen sulfide (H 2 S) adsorption from synthetic natural gas. The raw OFA was basically modified with a mixture of acids (20% nitric acid [HNO 3 ] and 80% phosphoric acid [H 3 PO 4 ]), and it was further treated with 2 M potassium hydroxide (KOH) to enhance the surface affinity as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The composition of Al-Fe-rich particles was similar to that of oil and coal fly ash emitted from local sources such as oil-and coal-fired boilers ( Figure 5), and similar in composition to oil and coal ash as reported in the scientific literature [66][67][68][69][70][71][72][73]. This makes it possible to use these values as source diagnostic ratios for source apportionment, regardless of study area location.…”
Section: Chemical Composition Of Potential Source Emissionssupporting
confidence: 73%
“…The composition of Al-Fe-rich particles was similar to that of oil and coal fly ash emitted from local sources such as oil-and coal-fired boilers ( Figure 5), and similar in composition to oil and coal ash as reported in the scientific literature [66][67][68][69][70][71][72][73]. This makes it possible to use these values as source diagnostic ratios for source apportionment, regardless of study area location.…”
Section: Chemical Composition Of Potential Source Emissionssupporting
confidence: 73%
“…Aslam et al concluded from the XRD analysis that HFOA consists of amorphous carbon and crystallites of metallic oxides, such as quartz, faujasite, aluminosilicate (mullite), zeolite, and cancrinite. [30] Similarly, other groups have reported the amorphous nature of carbon. [26,29,31,32,33,34] In contrast, Al Ghouti et al, using XRD analysis, reported that carbon in HFOA generated in a Jordanian thermal power plant was crystalline in nature.…”
Section: Structural Characterizationmentioning
confidence: 86%
“…[32] On the other hand, Aslam et al reported that the BET surface area of HFOA was 2.75 m 2 g À 1 with a pore size of 28.0 nm. [30] Figure 4. Typical SK edge XANES deconvoluted spectra of HFOA particles with < 2.5 μm and > 2.5 μm size.…”
Section: Physical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations